FeCoNi-NS-ACVs catalyst with high-activity oxygen evolution reaction and preparation method of FeCoNi-NS-ACVs catalyst

By designing the FeCoNi-NS-ACVs catalyst, combining two-dimensional nanosheets with three-dimensional porous structures, and performing cyclic voltammetry activation in the alkaline medium, the problem of lack of high-active electrocatalytic oxygen evolution reaction and cheap long-term stable catalyst in the prior art is solved, and good electrocatalytic performance and stability of OER in the alkaline medium is achieved.

CN119877021APending Publication Date: 2025-04-25CHINA UNIV OF PETROLEUM (EAST CHINA)
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510233715.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-28
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The lack of high-active electrocatalytic oxygen evolution reactions and cheap long-term stable catalysts in the prior art limits the improvement of the efficiency of electrocatalytic water decomposition and hydrogen production.

Method used

Through corrosion engineering, the FeCoNi-NS-ACVs catalyst is designed, combined with two-dimensional nanosheets and three-dimensional porous structures, and cyclic voltammetry activation is carried out in alkaline media to construct an electrocatalyst with a specific nanostructure.

Benefits of technology

It has achieved good electrocatalytic performance and stability for redox reaction (OER) in alkaline media, has superhydrophilic surface and low electrochemical resistance, and can maintain high catalytic activity and stability at current densities of 50mA cm-2 and 100mA cm-2.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119877021A_ABST
    Figure CN119877021A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electro-catalytic oxygen evolution (OER), and discloses a FeCoNi-NS-ACVs anode oxygen evolution electro-catalyst with efficient catalytic activity. The two-dimensional nanosheet with a three-dimensional porous nanostructure is synthesized by using the unique coordination structure and form of MOF in the presence of sodium sulfide through anode cyclic voltammetry scanning (ACVs), and meanwhile, the unique porous structure provides a higher electron transmission rate, so that the two-dimensional nanosheet has good electro-catalytic performance. The formed two-dimensional nanosheets provide combination of metal ions and sulfur ions in the ACV process to construct a layered form, and transportation of electrolyte and release of generated bubbles are facilitated. In addition, the prepared FeCoNi-NS-ACVs has the super-hydrophilicity and the excellent conductive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electrocatalytic oxygen evolution reaction, in particular to a FeCoNi-NS-ACVs catalyst with high activity for oxygen evolution reaction and a preparation method thereof. Background Art

[0002] As the use of fossil fuels causes increasingly serious environmental pollution, it is of great significance to vigorously develop sustainable green energy. Among them, hydrogen energy is considered to be an ideal energy storage medium to alleviate environmental pollution and energy crisis due to its high energy density and eco-friendly characteristics. Electrocatalytic water decomposition is the most environmentally friendly and ideal hydrogen production method that does not produce polluting gases. However, the electrocatalytic efficiency is limited by the slow reaction kinetics on the anode electrode. At present, precious metal-based nanomaterials have excellent performance, but there are problems of high cost and scarcity. Therefore, it is of great significance to explore efficient non-precious metal-derived oxygen evolution reaction (OER) catalysts with specific nanostructures to improve the overall efficiency of hydrogen production from water electrolysis.

[0003] Among the studied nanostructures, two-dimensional nanosheets are widely used in catalyst research due to their abundant exposed active sites, ultrathin morphology, and fast charge mobility, and can serve as an ideal substrate for constructing electrocatalysts. In addition to the two-dimensional morphology, the three-dimensional porous structure can expose abundant active sites during the electrocatalytic process, which is also beneficial to improve the electrocatalytic performance. In addition, the abundant channels are conducive to the transport of electrolytes and the release of generated gases, thereby accelerating the reaction kinetics. Therefore, the designed electrocatalysts with a combination of two-dimensional and three-dimensional morphologies will be a potential way to improve the catalytic activity. In addition to special nanostructures, the coupling effect between different metal ions is also a valuable strategy to improve the electrocatalytic performance. The performance of related materials combining composite structures and strategies as OER catalysts remains to be explored. Summary of the invention

[0004] In view of the current lack of highly active electrocatalytic oxygen evolution and inexpensive long-term stable catalysts, the purpose of the present invention is to provide an electrolytic OER catalyst with a highly active two-dimensional and three-dimensional composite structure.

[0005] The preparation method of the FeCoNi-NS-ACVs catalyst according to a specific embodiment of the present invention comprises the following steps:

[0006] (1) Preparation of FeCoNi-NS

[0007] Ni(NO3)2·6H2O, Co(NO3)2·6H2O and terephthalic acid are dissolved in a solvent to obtain solution a;

[0008] Solution a and sodium chloride solution are placed in a reactor containing foamed iron, and heated to react at 120-180° C. The product is washed and dried to obtain FeCoNi-NS;

[0009] (2) Using FeCoNi-NS as the working electrode, Pt foil as the counter electrode, and saturated calomel electrode (SCE) as the reference electrode, SCE was used for cyclic voltammetry to obtain the FeCoNi-NS-ACVs catalyst.

[0010] According to the preparation method of the FeCoNi-NS-ACVs catalyst of the specific embodiment of the present invention, in the solution a, the concentration of Ni(NO3)2·6H2O is 0.01-0.1M, and / or,

[0011] The concentration of Co(NO3)2·6H2O is 0.001-0.1M, and / or,

[0012] and terephthalic acid concentration is 0.01-0.1M.

[0013] Preferably, the concentration of Ni(NO3)2·6H2O is 0.03-0.04M, the concentration of Co(NO3)2·6H2O is 0.004-0.006M, and the concentration of terephthalic acid is 0.01-0.02M.

[0014] Preferably, solution a and sodium chloride solution are placed in a reactor containing foamed iron, and heated at 145-155° C. for 2-4 hours.

[0015] According to the preparation method of the FeCoNi-NS-ACVs catalyst according to a specific embodiment of the present invention, the solvent is one or more of N,N-dimethylformamide (DMF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), acetonitrile (CHCN), hexamethylphosphoramide (HMPA), and dimethylacetamide PC.

[0016] Preferably, the solvent is DMF.

[0017] According to the preparation method of the FeCoNi-NS-ACVs catalyst of the specific embodiment of the present invention, the concentration of the sodium chloride solution is 0.1-1 M. Preferably, the concentration of the sodium chloride solution is 0.05-0.07M.

[0018] According to the preparation method of the FeCoNi-NS-ACVs catalyst of the specific embodiment of the present invention, solution a and sodium chloride solution are placed in a reactor, and the reactor contains foamed iron, and the volume of the foamed iron is 2.0 cm*1.0 cm*0.1 cm.

[0019] According to the preparation method of the FeCoNi-NS-ACVs catalyst in a specific embodiment of the present invention, in a 0.5-2M KOH solution, at 5-15mV s -1 Cyclic voltammetry was performed at a scan rate from 0 to 1.3 V vs. SCE to obtain FeCoNi-NS-ACVs catalyst.

[0020] According to the method for preparing the FeCoNi-NS-ACVs catalyst according to a specific embodiment of the present invention, it is characterized in that the KOH solution contains 1-2g Na2S.

[0021] Preferably, 1.5 g Na2S is contained in 1 M KOH solution.

[0022] Preferably, 10mV s -1 The scan rate was from 0 to 1.3 V vs. SCE for 7 cycles to obtain the FeCoNi-NS-ACVs catalyst.

[0023] The present invention also provides a FeCoNi-NS-ACVs catalyst prepared according to the above preparation method.

[0024] The present invention designs a trimetallic two-dimensional nanosheet coupled with a three-dimensional nanostructure through corrosion engineering, and performs cyclic voltammetric activation (ACVs) in the presence of sodium sulfide on foamed iron. The constructed specific nanostructure is conducive to exposing active sites, providing abundant channels, and promoting mass transport. In addition, the designed FeCoNi-NS-ACVs has a superhydrophilic surface and low electrochemical resistance, which is the key to improving electrocatalytic performance. The results show that the FeCoNi-NS-ACVs electrocatalyst exhibits good electrocatalytic performance and stability for OER in alkaline media.

[0025] Beneficial effects of the present invention:

[0026] The present invention synthesizes a two-dimensional nanosheet with a three-dimensional porous nanostructure by using the unique coordination structure and morphology of MOF in the presence of sodium sulfide through anodic cyclic voltammetry scanning (ACVs). At the same time, the unique porous structure provides a faster electron transfer rate, which makes it have good electrocatalytic performance. The formed two-dimensional nanosheet provides metal ions and sulfur ions to combine to construct a layered morphology during the ACV process, which is beneficial to the transportation of electrolytes and the release of generated bubbles. In addition, the prepared FeCoNi-NS-ACVs has super hydrophilicity and excellent electrical conductivity. Based on the above advantages, FeCoNi-NS-ACVs has excellent OER electrocatalytic performance, at 50mA cm -2 and 100mA cm -2 The overpotentials at the current density are only 170mV and 198mV, which can drive 50mA cm-2 and 100mA cm -2 And it has higher stability.

[0027] The catalyst preparation method of the present invention is simple, the raw materials used are easy to purchase and prepare, easy to operate, and convenient for large-scale production; the catalyst of the present invention has significantly improved performance compared with the commercial catalyst RuO2, and has higher catalytic activity; the catalyst of the present invention has very high stability and can operate stably for more than 50 hours in different current density ranges.

[0028] The present invention develops 3D nanostructured FeCoNi-NS-ACVs based on trimetallic 2D nanosheets through corrosion engineering and ACVs for OER in alkaline media, in which the coupling effect between the introduced metal species and 2D nanosheets plays a key role in improving the electrocatalytic activity. In addition, the iron foam substrate has a multi-channel porous structure, which enables the transport of electrolytes and the timely release of generated bubbles to expose active sites. FeCoNi-NS-ACVs show excellent electrocatalytic performance and stability in OER and overall water splitting, providing a facile and scalable strategy for the development of non-precious metal-based nanomaterials for energy-related applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0030] Figure 1 The results of SEM and TEM studies on the morphology of the synthesized electrocatalysts are shown.

[0031] (a) SEM morphology of FeCoNi-NS-ACVs, (b) SEM image, (c) TEM image, (e) HRTEM image, (f) HAADF-STEM image, (g) corresponding element mapping of Fe, Co, Ni, S, C, and O in FeCoNi-NS-ACVs.

[0032] Figure 2 The results of FeCoNi-NS-ACVs are shown, where

[0033] XPS measurement spectra of Fe 2p (a), XPS measurement spectrum of Ni 2p (b), XPS measurement spectrum of Co 2p (c) and XPS measurement spectrum of S2p (d); (e) Raman spectra of FeCoNi-NS and FeCoNi-NS-ACVs; (f) contact angle measurement of FeCoNi-NS-ACVs.

[0034] Figure 3 Displays the results of electrochemical measurements, where

[0035] (a) OER polarization curve, (b) at 50 mA cm -2 and 100mA cm -2 The overpotential comparison under (c) overpotential (E j10 ) and Tafel slope comparison with references, (d) Nyquist plot, (e,f) stability test of the obtained catalyst in 1 M KOH.

[0036] Figure 4 is the Tafel slope of FeCoNi-NS-ACVs catalyst and comparative samples.

[0037] Figure 5 This is the stability test curve of the FeCoNi-NS-ACVs catalyst obtained in Example 1.

[0038] Figure 6 (a) LSV curves of FeCni-NS-ACVS / / F-FeCoP and catalyst after 52h stability test of total water splitting in 1M KOH (attached is a photo of the water splitting cell). (b) Solar cell driving overall water splitting. (c, d) Stability test of the obtained catalyst in 1M KOH. DETAILED DESCRIPTION

[0039] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0040] Example 1

[0041] 1.1 Preparation of FeCoNi-NS-ACVs catalyst

[0042] Iron foam (2.0 cm*1.0 cm*0.1 cm) was ultrasonically pretreated in 1 M HCl, acetone and anhydrous ethanol for 30 min to remove surface impurities.

[0043] Solution a: Ni(NO3)2·6H2O (0.14 g), Co(NO3)2·6H2O (0.022 g) and terephthalic acid (0.033 g) were dissolved in 15 mL DMF with stirring.

[0044] Solution b: NaCl (0.035 g) was dissolved in 1 mL of deionized water.

[0045] The two solutions were mixed and stirred and transferred to a 100 mL stainless steel autoclave reactor containing foamed iron. The mixture was heated in an oven at 150°C for 3 h, and the product was washed with anhydrous ethanol and deionized water several times, and then dried at 60°C for 12 h to obtain FeCoNi-NS.

[0046] FeCoNi-NS was used as the working electrode, Pt foil as the counter electrode, and saturated calomel electrode (SCE) as the reference electrode. -1 The scan rate was from 0 to 1.3 V vs. SCE for 7 cyclic voltammetry (CV) to obtain FeCoNi-NS-ACVs catalyst.

[0047] 1.2 The morphology of the synthesized electrocatalyst was studied by SEM and TEM.

[0048] The iron foam has a smooth surface and no specially modified nanomaterials, and forms two-dimensional nanosheets after solvothermal reaction ( Figure 1 a).

[0049] In the presence of 1 M KOH in sodium sulfide, after ACVs, in addition to the evolved 3D porous structure, the morphology of the 2D nanosheets was well maintained ( Figure 1 b).

[0050] The specific morphology composed of 2D and 3D nanostructures is conducive to the transport of electrolytes, exposing abundant active sites and multiple channels during electrocatalysis, which effectively improves the catalytic performance. However, it is not easy to characterize the specific composition of 3D porous species due to the close contact with 2D nanosheets. We believe that the porous species are composed of metal sulfides and metal hydroxides generated during the ACVs process, and the metal ions originate from the 2D nanosheets. That is, the metal ions released from the coordination structure react with sodium sulfide and hydroxide ions to generate metal sulfides and metal hydroxides.

[0051] The nanosheets can also be clearly observed from TEM images ( Figure 1 c, d), high-resolution TEM shows that the lattice spacings of the (121) plane of CoOOH, the (131) plane of FeOOH, and the (002) plane of Ni(OH) are 0.213 nm, 0.207 nm, and 0.231 nm, respectively. Figure 1e). In addition, elemental mapping showed that the Ni, Co, Fe, S, O, and C elements were uniformly distributed in the prepared FeCoNi-NS-ACVs ( Figure 1 g).

[0052] 1.3XPS measurements confirmed the presence of C, S, O, Fe, Co and Ni elements in FeCoNi-NS-ACVs.

[0053] For high resolution Fe2p( Figure 2 (a)), the peaks at 723.2eV, 711.5eV, 726.6eV, and 713.9eV are attributed to Fe, respectively. 3+ and Fe 2+ .

[0054] like Figure 2 As shown in b, Ni was found in the prepared FeCoNi-NS-ACVs. 3+ and Ni 2+ , whose peaks are 875.1eV, 857.1eV, 873.2eV, 855.6eV respectively. In addition, the peaks at 784.4eV, 774.7eV and 781.0eV are Co 2+ and Co 3+ The high-resolution S2p has three types of peaks, the peak at 168.4 eV corresponds to SO, and the peaks at 163.8 eV and 162.1 eV correspond to MS bonds ( Figure 2 (d)), indicating the successful synthesis of metal sulfides during the ACVs process. Raman measurements were performed to investigate the nanostructure evolution after ACVs.

[0055] like Figure 2 As shown in (e), after ACVs at 483.3 cm -1 and 686.5cm -1 Two new peaks appeared at , which are related to metal hydroxides and are generally considered to be active species in the OER process.

[0056] like Figure 2 As shown in (f), the prepared FeCoNi-NS-ACVs have superhydrophilicity, so they can be in close contact with the electrolyte to accelerate the reaction kinetics. In the present invention, a small amount of NaCl is added to partially corrode the iron mesh to release iron ions. With Ni as the main active site, the electron distribution and transfer are optimized, and the intrinsic activity of the catalyst is adjusted by elements such as Fe and Co.

[0057] Comparative Example 1

[0058] Solution a: The difference from Example 1 is that only phthalic acid (0.033 g) was dissolved in 15 mL of DMF under stirring.

[0059] Solution b: Same as Example 1.

[0060] The other steps were the same as those in Example 1 to prepare a Fe-S catalyst.

[0061] Comparative Example 2

[0062] Solution a: The difference from Example 1 is that it does not contain phthalic acid, that is, Ni(NO3)2·6H2O (0.14 g) and Co(NO3)2·6H2O (0.022 g) are dissolved in 15 mL DMF under stirring.

[0063] Solution b: Same as Example 1.

[0064] The other steps were the same as those in Example 1 to prepare a FeCoNi-S catalyst.

[0065] Comparative Example 3

[0066] Solution a: The difference from Example 1 is that it does not contain Co(NO3)2·6H2O, that is, Ni(NO3)2·6H2O (0.14 g) and terephthalic acid (0.033 g) are dissolved in 15 mL DMF under stirring.

[0067] Solution b: NaCl (0.035 g) was dissolved in 1 mL of deionized water.

[0068] The other steps are the same as those in Example 1, and the specific steps are as follows:

[0069] The two solutions were mixed and stirred and transferred to a 100 mL stainless steel autoclave reactor containing foamed iron, heated in an oven at 150°C for 3 h, washed with anhydrous ethanol and deionized water several times, and dried at 60°C for 12 h to obtain FeNi-NS.

[0070] FeNi-NS was used as the working electrode, Pt foil as the counter electrode, and saturated calomel electrode (SCE) as the reference electrode. -1 The scan rate was from 0 to 1.3 V vs. SCE for 7 cyclic voltammetry (CV) to obtain FeNi-NS-ACVs catalyst.

[0071] Comparative Example 4

[0072] Solution a: The difference from Example 1 is that it does not contain Ni(NO3)2·6H2O, that is, Co(NO3)2·6H2O (0.022 g) and terephthalic acid (0.033 g) are dissolved in 15 mL DMF under stirring.

[0073] Solution b: NaCl (0.035 g) was dissolved in 1 mL of deionized water.

[0074] The other steps are the same as those in Example 1, and the specific steps are as follows:

[0075] The two solutions were mixed and stirred and transferred to a 100 mL stainless steel autoclave reactor containing foamed iron. The mixture was heated in an oven at 150°C for 3 h, and the product was washed with anhydrous ethanol and deionized water several times and then dried at 60°C for 12 h to obtain FeCo-NS.

[0076] FeCo-NS was used as the working electrode, Pt foil as the counter electrode, and saturated calomel electrode (SCE) as the reference electrode. -1 The scan rate was from 0 to 1.3 V vs. SCE for 7 cyclic voltammetry (CV) to obtain the FeCo-NS-ACVs catalyst.

[0077] Synthesis of HER electrode of F-FeCoP: Co(NO3)2·6H2O and NHF4 were placed in the bottom of the bottle, iron foam was added, and the mixture was placed in an oven at 120°C for 12 hours. Afterwards, the mixture was cooled naturally at room temperature and washed several times with anhydrous ethanol and deionized water to remove the unreacted products. Then, sodium hypophosphite and precatalyst were placed in an argon environment in the upstream and downstream, respectively, to obtain F-FeCoP (350°C, 2 hours).

[0078] Electrochemical data of oxygen evolution reaction

[0079] The electrocatalytic OER performance of the prepared FeCoNi-NS-ACVs and reference samples was tested by a typical three-electrode setup under 1 M KOH conditions.

[0080] like Figure 3 As shown in ab, FeCoNi-NS-ACVs reaches 50 mA cm -2 and 100mA cm -2 The required polarization potentials are 170 mV and 198 mV, respectively, which are better than the RuO2 benchmark catalyst and some reported values ​​( Figure 3 c). Relatively speaking, the bimetallic FeNi-NS-ACVs and FeCo-NS-ACVs exhibited poor catalytic activity and had higher overpotentials relative to the trimetallic FeCoNi-NS-ACVs, indicating that the coupling effect of the introduced metal species plays a crucial role in promoting the catalytic performance. In addition, FeCoNi-S has a larger overpotential (250 mV@50 mAcm) relative to FeCoNi-NS-ACVs in the potential range studied. -2 and 273mV@100mA cm -2 ).

[0081] Tafel diagram Figure 4 ) verified that FeCoNi-NS-ACVs is higher than FeCoNi-S (78mV dec -1 ) has a smaller value (64mV dec -1 ), indicating that the kinetics of the sample is faster.

[0082] Therefore, the constructed 2D nanosheets play a key role in promoting the catalytic process because the specific nanostructure is conducive to the transport of electrolytes and the release of generated bubbles. The electrochemical impedance spectroscopy (EIS) results of the synthesized samples are shown in Figure 2. Figure 3 d. It is well known that the conductivity of the catalytic electrode directly affects the electrocatalytic activity. Among the prepared electrocatalysts, the conductivity of the catalytic electrode is the best. FeCoNi-NS-ACVs exhibits the lowest charge transfer resistance during the electrocatalytic OER process.

[0083] In addition to its remarkable catalytic activity, FeCoNi-NS-ACVs also has good long-term stability. Figure 3 As shown in e and f, the current density increases with the increase of the applied potential, and then maintains well during the reverse process, indicating its outstanding stability and long-term stability for OER of more than 50 h.

[0084] The stability of FeCoNi-NS-ACVs was tested by SEM and XPS measurements. Figure 5 shown.

[0085] FeCoNi-NS-ACVs maintained good three-dimensional porosity after stability testing, indicating that its nanostructure is strong. There was no obvious change in the XPS graph of FeCoNi-NS-ACVs after OER testing, proving that it is very stable. Therefore, all the data confirm the great potential of FeCoNi-NS-ACVs as practical electrocatalysts for OER.

[0086] Overall water splitting measurements

[0087] A complete water electrolysis device was established with the prepared FeCoNi-NS-ACVs and F-FeCoP as anode and cathode, respectively. Figure 6 b).

[0088] like Figure 6 As shown in a, low voltages of 1.37 V and 1.58 V are required to achieve 10 mA cm -2 and 100mA cm -2 The current density of the designed FeCoNi-NS-ACVs is better than that of many other available catalysts. In addition, the designed FeCoNi-NS-ACVs also exhibit excellent stability in overall water splitting through multi-step measurements ( Figure 6c, d).

[0089] As mentioned above, the trimetallic nanosheet-derived nanomaterials FeCoNi-NS-ACVs exhibit excellent electrocatalytic performance, which can be attributed to the following factors: the specific nanostructure constructed by 2D and 3D morphologies can expose abundant active sites, which is beneficial to the transport of electrolytes; the coupling effect of the introduced metal species also plays an important role in improving the catalytic activity; superhydrophilicity and low electrochemical resistance properties are key factors in the electrocatalytic process; the iron foam substrate with porous nanostructure provides abundant channels for the release of generated bubbles.

[0090] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing a FeCoNi-NS-ACVs catalyst, characterized in that: The preparation method comprises the following steps: (1) Preparation of FeCoNi-NS Ni(NO3)2·6H2O, Co(NO3)2·6H2O and terephthalic acid are dissolved in a solvent to obtain solution a; Solution a, sodium chloride solution and foamed iron are placed in a reactor, heated at 120-180° C. for reaction, and the product is washed and dried to obtain FeCoNi-NS; (2) Using FeCoNi-NS as the working electrode, Pt foil as the counter electrode, and saturated calomel electrode (SCE) as the reference electrode, SCE was used for cyclic voltammetry to obtain the FeCoNi-NS-ACVs catalyst.

2. The method for preparing the FeCoNi-NS-ACVs catalyst according to claim 1, characterized in that: In solution a, the concentration of Ni(NO3)2·6H2O is 0.01-0.1M, and / or, The concentration of Co(NO3)2·6H2O is 0.001-0.1M, and / or, and terephthalic acid concentration is 0.01-0.1M.

3. The preparation method of the FeCoNi-NS-ACVs catalyst according to claim 1, characterized in that: The solvent is one or more of N,N-dimethylformamide, dimethyl sulfoxide, N-methylpyrrolidone, acetonitrile, hexamethylphosphoramide and dimethylacetamide.

4. The method for preparing the FeCoNi-NS-ACVs catalyst according to claim 1, characterized in that: The concentration of the sodium chloride solution is 0.1-1M.

5. The method for preparing the FeCoNi-NS-ACVs catalyst according to claim 1, characterized in that: In 0.5-2M KOH solution, at 5-15mV s -1 Cyclic voltammetry was performed at a scan rate from 0 to 1.3 V vs. SCE to obtain FeCoNi-NS-ACVs catalyst.

6. The method for preparing the FeCoNi-NS-ACVs catalyst according to claim 5, characterized in that: KOH solution contains 1-2g Na2S.

7. The FeCoNi-NS-ACVs catalyst prepared by the preparation method according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Ferronickel hydrotalcite-like / ferronickel sulfide heterostructure seawater oxidation electrocatalyst and preparation method thereof

    CN114657591A

  • NiCo-OH / FeOOH heterostructure nanosheet as well as preparation method and application thereof

    CN119194502A